"Are you asking me or are you telling me?": Expertise, evidence, and blame attribution in a post-game interview. (October 2021) - Lindwall, Oskar; Lynch, Michael
This paper is an analysis of a video clip of an interview between a reporter and ice hockey player following a game in which the player was involved in a hard collision with a member of the opposing team. The paper explores blame attribution and how participants claim and disclaim expertise in a way that supports or undermines assertions to have correctly seen and assessed the actions shown on tape. Our analysis focuses on the video of the interview, and it also examines relevant video clips of the collision and various commentaries about the identities of the characters and their actions shown on the videos. In brief, the study is a third-order investigation of recorded-actions-under-analysis. It uses the videos and commentaries as "perspicuous phenomena" that illuminate and complicate how the members' own action category analysis is bound up with issues of expertise, evidence, and blame.